The good politician folk theories, political interaction, and the rise of anti-politics - Clarke, Nick 1974- (Cambridge University Press, 2018)
Surveys show a lack of trust in political actors and institutions across much of the democratic world. Populist politicians and parties attempt to capitalise on this political disaffection. Commentators worry about our current 'age of anti-politics'. Focusing on the United Kingdom, using responses to public opinion surveys alongside diaries and letters collected by Mass Observation, this book takes a long view of anti-politics going back to the 1940s. This historical perspective reveals how anti-politics has grown in scope and intensity over the last half-century. Such growth is explained by citizens' changing images of 'the good politician' and changing modes of political interaction between politicians and citizens. Current efforts to reform and improve democracy will benefit greatly from the new evidence and conceptual framework set out in this important study
Title from publisher's bibliographic system (viewed on 27 Apr 2018)
Table of contents -- List of figures -- List of tables -- Preface: the long road to 2016, brexit, and trump -- Introduction -- The problem of anti-politics -- Taking the long view and listening to citizens' voices -- Beyond trendless fluctuation: the broadening social scope of anti-politics -- Beyond permanent apathy: the broadening political scope of anti-politics -- Beyond the decline of deference: the rising intensity of anti-politics -- Beyond depoliticisation: the persistent force of stealth democratic folk theories -- Changing images of the good politician -- Changing modes of political interaction -- Changing folk theories: from stealth democracy to stealth populism -- Conclusion -- Appendix -- References -- Index
Keywords: Political participation; Apathy / Political aspects; Populismus; Politikverdrossenheit; Politische Elite; Vertrauenswürdigkeit; Öffentliche Meinung; Politiker; Großbritannien